Clinical profile of patients with ischemic cardiopathy and rheumatoid arthritis. Centro Cardiovascular Regional Centro Occidental (Boletin Médico de Postgrado, 2020)
Ischemic heart disease is the most frequent cause of morbidity and mortality worldwide. Rheumatoid arthritis (RA) is associated with premature development of cardiovascular disease and life expectancy is mainly reduced due to an increase in cardiovascular death. A descriptive and retrospective review of medical charts was conducted with the objective of describing the clinical profile of patients with ischemic heart disease and RA who attended the Unidad de Prevención Secundaria y Rehabilitación Cardiovascular del Centro Cardiovascular Regional Centro Occidental from January 2013 to December 2018. 37 patients with RA diagnosis who presented a coronary event were included. The results show that 62% of patients were female with a mean age of 59 ± 11 years; 65% had less than 10 years of diagnosis of RA. Sedentary lifestyle represented the most frequent factor (92%), followed by HTA (76%), smoking (73%), DM (43%), family history of ischemic heart disease (24%), obesity (22%), dyslipidemia (16%) and finally CKD (11%); the most frequent type of coronary event was the IMsEST (43%). The multivariate analysis showed no statistically significant relationship between the number of risk factors and the duration of RA with the presence of coronary lesions. Sedentary lifestyle was the most frequent risk factor in this population however the behavior of traditional risk factors for ischemic heart disease in patients with RA does not differ from the general population.
Keywords: rheumatoid arthritis; ischemic heart disease; risk factors; sedentary lifestyle; hypertension